Bisindolization Reaction Employing Phthalimide-N-sulfonic Acid as an Efficient Catalyst - Banari, Hoda; Kiyani, Hamzeh; Pourali, Ali R. (Current Organocatalysis, 2020)
Background: Bis(indolyl) methanes (BIMs) have a wide spectrum of applications in biomedicine and agriculture as well as are present in natural products. These bisheterocyclic compounds possess vast pharmacological, including antifungal, antitubercular, anti-inflammatory, antibacterial, anticancer, anticonvulsant, antibiotic, antiviral, antimalarial, analgesic, and antidiabetic properties. BIMs scaffolds have also been employed as selective optical chemosensors for detection of some anions and cations with the naked eye. Because of the importance of these bisheterocycles, various methods have been reported for their synthesis through reaction of indole derivatives and aldehydes or ketones. Therefore, the synthesis of BIMs through different methodologies has received widespread attention in the field of organic synthesis and medicinal chemistry. Objective: In this study, the catalytic activity of phthalimide-N-sulfonic acid (PISA) as an efficient and safe solid acidic organocatalyst toward the synthesis of BIMs derivatives in ethanol is described. Methods: Indole derivatives (2 mmol), aryl/heteroaryl aldehydes (1 mmol), and PISA (10 mol%) were mixture in ethanol. The reaction mixture was stirred at room temperature for the appropriate times. After workup and separation of catalyst, the corresponding heterocyclic products were obtained through recrystallization from hot ethanol. Results: The BIMs derivatives were easily obtained via Bisindolization Reaction (BIR) of two indoles (2-methylindole and indole) with a series of aryl and heteroaryl aldehydes. The BIR was efficiently catalyzed at room temperature using PISA as an excellent organocatalyst under optimized reaction conditions. Conclusion: The reactions were implemented in simple manner and were completed within acceptable reaction times. The expected BIM products were obtained in satisfactory yields. The catalyst can be recovered and reused several times in the template reaction. This approach provides the benefits of convenience, simple operational procedure, no use of hazardous organic solvents, cheapness and ease of preparation of catalyst.
Keywords: Bis(indolyl)methanes